BENEFICIAL EFFECTS OF DIFFERENT EXTRACTS OF MOMORDICA DIOICA SEED ON LIPID PROFILE STATUS IN STREPTOZOTOCIN INDUCED DIABETIC RATS - P SAILAJA RAO; G KRISHNA MOHAN (International Journal of Pharma and Bio Sciences, 2015)
Diabetes mellitus is one of the widespread and severe metabolic disorders in human all over the world. The present study was designed to evaluate the potential anti- hyperlipidemic efficacy of chloroform and ethylacetate extracts ofMomordica dioica seeds in diabetic rats. Diabetes was induced by giving Streptozotocin intraperitoneally, rats which showed blood glucose levels of >250 mg/dlwere selected for the study. Different extracts wereadministered at a dose of 200 mg/kg orally and blood glucose levelswere estimated by glucose-oxidase method. Metformin (50 mg/kg) was administered as standard oral hypoglycaemic agent. The plasma levels of low density lipoproteins (LDL), very low density lipoproteins (VLDL), cholesterol (CH) and triglycerides (TG) were estimated and found to be significantly (p<0.0001) lowered in diabetic rats. The results showed that the present study provided a rationale for the use of Momordica dioica seed extracts as an anti-diabetic agent and anti-hyperlipidemic agent.